The regulation of interconnection and regulatory alignment in the Southern African Development Community - Grace Nsomba (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper analyses interconnection in telecommunications markets in the Southern African Development Community (SADC) region, focusing on cross-border roaming as well as international interconnection. These issues have been identified as critical for cross-border integration and regulatory alignment. The paper argues for a greater alignment of regulatory approaches across the SADC region to promote competition, lower prices, and innovation. This is done by investigating the regional experience in terms of the cross-country integration of telecommunications markets through international calls and roaming services. The investigation and analysis find that there are currently low levels of alignment in regulation between SADC member states thanks to varying national policies across various countries. In addition, information regarding operator costs is asymmetric, making regulation challenging, as this affects the extent to which the relationship between costs and retail prices can be observed and regulated. Direct consultation between the SACD, regulators, competition agencies, and other stakeholders is recommended in order to address these issues. Another important finding is that advances in technology have meant significant increases in demand for broadband and data services, resulting in a surge in demand for over-the-top services. Attention therefore needs to be paid to the harmonization of regulation regarding Internet-related services. Here, fixed services can play a valuable role in providing high speeds and high volumes of data at a lower cost, which is important considering the difficulties that landlocked SADC countries face in providing low-cost Internet services.
Keywords: L51; L96; 330; Southern African Development Community; interconnection; competition; regulation; telecommunications